ta có : \(A=3+3^2+3^3+...+3^{2008}\)
\(\Rightarrow3A=3\left(3+3^2+3^3+...+3^{2008}\right)\)
\(3A=3^2+3^3+3^4+...+3^{2009}\)
\(\Rightarrow3A-A=2A=\left(3^2+3^3+3^4+...+3^{2009}\right)-\left(3+3^2+3^3+...+3^{2008}\right)\)
\(2A=3^{2009}-3\) \(\Rightarrow2A+3=3^{2009}-3+3=3^{2009}=3^x\)
\(\Rightarrow x=2009\) vậy \(x=2009\)
\(A=3+3^2+3^3+....+3^{2008}\)
\(\Leftrightarrow3A=3^2+3^3+3^4+....+3^{2009}\)
\(\Leftrightarrow3A-A=\left(3^2+3^3+3^4+....+3^{2009}\right)-\left(3+3^2+3^3+....+3^{2008}\right)\)
\(\Leftrightarrow2A=3^{2009}-3\)
\(\Leftrightarrow2A+3=3^x=3^{2009}-3+3=3^{2009}\)
Vậy x=3 để \(2A+3=3^x\)